Female Muslim Jobseekers in Australia: Liminality, Obstacles and Resilience - Nilan, Pam; Samarayi, Ibtihal; Lovat, Terence (International Journal of Asian Social Science, 2012)
This article analyses obstacles faced by female Muslim jobseekers in Australia using the theoretical framework of liminality suggested by Homi Bhabha. Interviews were conducted with 21 female Muslim refugees and migrants of varying ages from 10 sending countries. Australia has long been a multicultural society, economically dependent on the labour of repeated waves of migration. Engagement with the labour market provides not only income but a sense of belonging in the receiving country. Yet these women faced substantial obstacles in their search for work. Nevertheless, they showed resilience in the face of repeated disappointment, and dedication to the task.